Safety and Effectiveness of Blonanserin in Chinese Patients with Schizophrenia: An Interim Analysis of a 12-Week Open-Label Prospective Multi-Center Post-marketing Surveillance - Wu, Haishan; Wang, Xijin; Liu, Xuejun; Sang, Hong; Bo, Qijing; Yang, Xiaodong; Xun, Zhiyuan; Li, Keqing; Zhang, Ruiling; Sun, Meijuan; Cai, Duanfang; Deng, Huaili; et al. (Frontiers in Psychiatry, 2022)
Schizophrenia is an unexplained, complex and serious mental illness. Blonanserin (BNS) is a new antipsychotic drug widely used in the treatment of schizophrenia. However, large-scale clinical studies have not been conducted in China. A multi-center, prospective, open-label, 12-week surveillance was carried out to evaluate the safety and effectiveness of BNS in patients with schizophrenia in China. Safety assessments included adverse drug reactions (ADRs), extrapyramidal symptoms (EPS), akathisia, concomitant medications for EPS by the end of treatment, and the changes in body weight from baseline by the end of treatment. The effectiveness was evaluated by the Brief Psychiatric Rating Scale (BPRS). From September 2018 to May 2020, of the 1,060 patients enrolled, 1,018 were included in the full analysis set (FAS) and safety set (SS), respectively. ADRs were developed in 205 patients among the included, the incidence being 20.1%. ADRs of EPS occurred in 169 patients, the incidence being 16.6%, ADRs of akathisia occurred in 90 patients, the incidence being 8.8%; concomitant therapeutic and prophylactic agents for EPS accounts for 19.2%; 4.0% of patients had a ≥7% increase in body weight from baseline at 12 weeks after initiating treatment. Using the last-observation-carried-forward (LOCF) method, the changes in total BPRS scores were −11.2 ± 10.17 (N = 1,018), −16.8 ± 12.69 (N = 1,018) and −20.6 ± 13.99 (N = 1,018) after 2/4, 6/8, or 12 weeks, respectively. 53.5% (545/1,018) patients showed response to blonanserin treatment in week 12. The post-marketing surveillance results of BNS demonstrates safety profile and effectiveness of the drug.